2018
DOI: 10.3233/kca-180028
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Imaging for Solid Renal Tumors: A Pictorial Review

Abstract: Abstract. The prognosis of renal tumors depends on histologic subtype. The increased use of abdominal imaging has resulted in an increase in the number of small renal incidentaloma in recent decades. Of these incidentally discovered tumors, 20% are benign lesions warranting conservative management, but most are renal cell carcinomas that warrant a more aggressive therapeutic approach due to their malignant potential. Dedicated diagnostic renal imaging is important for characterization of renal tumors to facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 84 publications
0
86
0
5
Order By: Relevance
“…In our preliminary report, we applied 1 H NMR and gas chromatography mass spectrometry (GCMS) based metabolomics analyses to urine and serum specimens to differentiate between benign and malignant renal masses in a small patient cohort (53 samples). In that study, we found that glycolytic and TCA cycle metabolites in blood and urine significantly separated benign lesions from ccRCC [11]. The present study is aimed at validating this previously identified urinary metabolic signature within a larger, external RCC cohort (Vanderbilt Cohort) in addition to exploring the metabolic differences between histologic subtypes of RCC.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our preliminary report, we applied 1 H NMR and gas chromatography mass spectrometry (GCMS) based metabolomics analyses to urine and serum specimens to differentiate between benign and malignant renal masses in a small patient cohort (53 samples). In that study, we found that glycolytic and TCA cycle metabolites in blood and urine significantly separated benign lesions from ccRCC [11]. The present study is aimed at validating this previously identified urinary metabolic signature within a larger, external RCC cohort (Vanderbilt Cohort) in addition to exploring the metabolic differences between histologic subtypes of RCC.…”
Section: Introductionmentioning
confidence: 80%
“…Secondly, benign lesions were compared with samples of ccRCC histology, a comparison most closely related to the groups compared in our previous study in which 92.5% of the RCC samples analyzed were ccRCC [11]. Distinct group separations were confirmed (Figure 2) and the metrics were similar to previously reported data; whereby, benign versus pT1 (R2Y = 0.42; Q2 = 0.27; Figure 2a) and benign versus pT2 showed the best group separation without overlap between the groups (R2Y = 0.96; Q2 = 0.82; Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent presenting symptoms were abdominal lump or mass (28, 93.33%) followed by abdominal pain (26,86.67%), weight loss (25, 83.33%), anorexia (20, 66.67%), fever (19, 63.33%), jaundice (18, 60.00%), hematuria (12, 40.00%) and others ( Table 2). Many clinical presentations occurred in combination like abdominal mass with abdominal pain.…”
Section: Resultsmentioning
confidence: 99%
“…25 CT scan has the advantage over ultrasound in accurately delineating a renal mass and differentiating pseudomasses and anatomical variants. 26 Following the treatment of renal masses, CT scan is the method of choice for post nephrectomy renal fossa surveillance. 27 CT is better than ultrasound in staging of Wilm's tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is not recommended for routine clinical practice but may provide additional information on venous involvement by tumour thrombus. However, for tumours sized ≤ 20 mm in diameter, gadoliniumenhanced sequences with fat saturation have been shown to be more sensitive than contrast-enhanced CT [7].…”
Section: Diagnosismentioning
confidence: 99%